PRODUCTIVITY OF GROUNDNUT FARMERS IN NIGER STATE, NIGERIA: GENDER DIFFERENTIAL ANALYSIS - OJO , A.O.; IBEH , A.M.; OJO , M.A.; ADEBAYO , C.O.; OSEGHALE , A.I. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
Poor productivity and gender disparities in agricultural production have hampered agro-industrial development and inclusive economic growth in Nigeria. The paper determined the productivity differentials in terms of efficiency estimates and scores, the scale of operation and the challenges faced by groundnut farmers along gender lines in the area. 132 groundnut farmers were randomly selected with, descriptive statistics and Data Envelopment Analysis (DEA) as analytical tools. Findings revealed that the farmers operated on a small-scale level. The mean efficiency estimates showed that female farmers (0.97) performed better than male farmers (0.94) under pure technical efficiency while male farmers were better under scale efficiency (0.93) than female farmers (0.89). The highest proportion of the farm groups was efficient under variable return to scale. The overall performance showed that female farm groups performed better in all three categories of efficiency measures than male groups. The analysis of the input slack revealed that 21 male groundnut farms and 10 female groundnut farms could reduce total expenditure on the farmland by 1.21% and 0.94%, respectively, without reducing their current level of production. Capital inputs, fertilizer, and seeds (male groups) and, capital inputs, farm size, and labour (female group) were the most excessively used inputs in the area. The major constraints facing the farmers were the unavailability of machinery for hire and the high cost of machinery. To scale up their productivity level, the farmers should be equipped with relevant and modern but subsidized production technologies through different intervention programs by the government and all the relevant stakeholders.